2018
DOI: 10.1002/jbm.a.36372
|View full text |Cite
|
Sign up to set email alerts
|

Tissue engineering of human knee meniscus using functionalized and reinforced silk‐polyvinyl alcohol composite three‐dimensional scaffolds: Understanding the in vitro and in vivo behavior

Abstract: Tissue engineered constructs with rapid restoration of mechanical and biological properties remain a challenge, emphasizing the need to develop novel scaffolds. Here, we present a multicomponent composite three-dimensional scaffold structure with biomimetic reinforcement and biomolecule functionalization for meniscus tissue engineering. The scaffold structure was developed using 3:1 silk fibroin (SF) and polyvinyl alcohol (PVA). Autoclaved eggshell membrane (AESM) powder (1-3%w/v) was used as reinforcement to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 30 publications
0
21
0
Order By: Relevance
“…One example is silk fibroin from silk worms, with seemingly improved biocompatibility and mechanical properties in comparison to non-biological polymers and increased similarity to the native meniscus [48,49,50]. A composite 3:1 ratio of silk fibroin and polyvinyl alcohol was shown to have good tissue ingrowth and ECM secretion in vitro, as well as being nontoxic in vivo [51]. Hydrogels also have important potential and have been shown to promote higher levels of ECM secretion than polycaprolactone alone.…”
Section: Discussionmentioning
confidence: 99%
“…One example is silk fibroin from silk worms, with seemingly improved biocompatibility and mechanical properties in comparison to non-biological polymers and increased similarity to the native meniscus [48,49,50]. A composite 3:1 ratio of silk fibroin and polyvinyl alcohol was shown to have good tissue ingrowth and ECM secretion in vitro, as well as being nontoxic in vivo [51]. Hydrogels also have important potential and have been shown to promote higher levels of ECM secretion than polycaprolactone alone.…”
Section: Discussionmentioning
confidence: 99%
“…Along with other biodegradable polymers such as polycaprolactone (PCL) [6] and polyvinyl alcohol (PVA), polylactic acid (PLA) is one of the most exploited scaffold material for TE applications [7,8]. Recent investigations on PLA scaffolds have focused on the optimization of their cell adhesion properties [9].…”
Section: Introductionmentioning
confidence: 99%
“…Silk fibroin (SF), a kind of natural protein derived from silkworm cocoons, is a widely used as one of the most popular materials for biomedical applications due to its distinct biological properties [ 1 , 2 ], such as good biocompatibility, biodegradability, good cell adhesion and non-toxicity [ 3 , 4 ]. In recent years, many researches have shown that SF biomaterials can be applied widely in tissue engineering scaffolds [ 5 , 6 ], blood vessel tissue engineering [ 7 ], bone tissue engineering [ 8 ], drug delivery systems, and so on [ 9 , 10 , 11 , 12 ]. Through being dissolved and purified, SF obtained from degummed silk can be used to prepare a variety of biomaterials, such as membranes, gels and fibers.…”
Section: Introductionmentioning
confidence: 99%